2009
DOI: 10.1109/mcg.2009.37
|View full text |Cite
|
Sign up to set email alerts
|

Using a Virtual Body to Aid in Exergaming System Development

Abstract: A framework for simulating physiological responses to exercise lets exergame developers more efficiently test their games during development. An example implementation combines software that simulates heart-rate responses with a custom hardware setup. Simulated heart-rate responses closely match the real physiological responses, demonstrating the approach's validity and potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Advanced methods that enable game designers to simulate the physiological responses of players in the development and testing stages may also facilitate the creation of optimized systems to maximize the health benefits of the AVGs of the future. 55…”
Section: Energy Expenditure Associated With Avg Play In the Home Settingmentioning
confidence: 99%
“…Advanced methods that enable game designers to simulate the physiological responses of players in the development and testing stages may also facilitate the creation of optimized systems to maximize the health benefits of the AVGs of the future. 55…”
Section: Energy Expenditure Associated With Avg Play In the Home Settingmentioning
confidence: 99%
“…The core idea is to use kinesthetic feedback to increase the game's difficulty for the stronger player. Sinclair et al [27] have suggested a similar idea; but did not implement or test it. We illustrate this idea through the Truck Pull exergame, presented below.…”
Section: Balancing Group Exercisementioning
confidence: 99%
“…Exerciser may need to maintain their heart rate at a target level. Sinclair et al [16] advocate that exergame should take the guidelines of American College of Sports Medicine as a scientific guarantee of true health, but few exergame abided it strictly.…”
Section: Exergame For Fitness Trainingmentioning
confidence: 99%